Interfacial Engineering of Ni/V2O3 Heterostructure Catalyst for Boosting Hydrogen Oxidation Reaction in Alkaline Electrolytes - Duan, Yu; Zhang, Xiao‐Long; Gao, Fei‐Yue; Kong, Yuan; Duan, Ying; Yang, Xiao‐Tu; Yu, Xing‐Xing; Wang, Yan‐Ru; Qin, Shuai; Chen, Zhi; Wu, Rui; Yang, Peng‐Peng; et al. (Angewandte Chemie International Edition, 2023)
Alkaline fuel cells can permit the adoption of platinum group metal‐free (PGM‐free) catalysts and cheap bipolar plates, thus further lowering the cost. With the exploration of PGM‐free hydrogen oxidation reaction (HOR) catalysts, nickel‐based compounds have been considered as the most promising HOR catalysts in alkali. Here we report an interfacial engineering through the formation of nickel‐vanadium oxide (Ni/V2O3) heterostructures to activate Ni for efficient HOR catalysis in alkali. The strong electron transfer from Ni to V2O3 could modulate the electronic structure of Ni sites. The optimal Ni/V2O3 catalyst exhibits a high intrinsic activity of 0.038 mA cm−2 and outstanding stability. Experimental and theoretical studies reveal that Ni/V2O3 interface as the active sites can enable to optimize the hydrogen and hydroxyl bindings, as well as protect metallic Ni from extensive oxidation, thus achieving the notable activity and durability. An interfacial engineering approach was developed to fabricate a low‐cost Ni/V2O3 heterostructure catalyst, which can efficiently and stably catalyze the hydrogen oxidation reaction (HOR) in alkaline media. Experimental and theoretical studies reveal that the Ni/V2O3 interface sites can optimize the hydrogen and hydroxyl bindings, as well as protect metallic Ni from extensive oxidation, thus achieving the notable HOR performance.